RISK ASSESSMENT OF THE CURRENT HANDLING OF MEDICAL WASTE IN HOSPITALS OF SANA'A CITY, YEMEN - Alwabr, Gawad M; Al-Mikhlafi, Ahmed S; Al-Hakimi, Saif A; Dughish, Munira A (MATTER: International Journal of Science and Technology, 2017)
Waste that is generated from healthcare establishments is potentially harmful to human beings and the environment. The objective of this study is to assess the environmental and health risk associated with processes of the current handling of medical waste in hospitals of Sana'a city, Yemen. The observations and follow up with the current handling of medical waste were done through frequent visits to the studied hospitals. A preliminary risks analysis (PRA) technique was applied as an analysis tool to identify and to evaluate the potential hazards of the activities and processes of the current handling of medical waste in the studied hospitals. Eighteen events related to containment, segregation, collection, transportation, waste storage, and waste treatment were analyzed. The results obtained in this study showed that 89% of the events of waste handling processes, which have been analyzed, were in high-risk levels. All events were in high-risk levels, suggesting a need to prioritize all these processes' events. For minimizing or interrupting the potential risks of the current handling of hospitals waste, the hospitals' management and the relevant ministries in the Yemeni government should cooperate to develop a comprehensive plan for management of medical waste, taking into account the results of this study.